2021
DOI: 10.1186/s13075-021-02663-z
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of myeloid-derived suppressor cells contributes to metabolic osteoarthritis through subchondral bone remodeling

Abstract: Background Osteoarthritis (OA) subsequent to acute joint injury accounts for a significant proportion of all arthropathies. Myeloid-derived suppressor cells (MDSCs) are a heterogeneous population of myeloid progenitor cells classically known for potent immune-suppressive activity; however, MDSCs can also differentiate into osteoclasts. In addition, this population is known to be expanded during metabolic disease. The objective of this study was to determine the role of MDSCs in the context of O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…The primary cytokines associated with the Th2 subset are interleukin-4 (IL-4) and IL-13. The Th17 phenotype has the capability to generate IL-17, which in turn triggers an autoimmune response and stimulates the activation of neutrophils [ 55 ]. Follicular helper T cells have the capability to express a range of genes associated with inflammation and can additionally stimulate B cells to generate immunoglobulin [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The primary cytokines associated with the Th2 subset are interleukin-4 (IL-4) and IL-13. The Th17 phenotype has the capability to generate IL-17, which in turn triggers an autoimmune response and stimulates the activation of neutrophils [ 55 ]. Follicular helper T cells have the capability to express a range of genes associated with inflammation and can additionally stimulate B cells to generate immunoglobulin [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies reported that subchondral bone sclerosis could be one of the major reasons that cause aging-related OA and that the abnormal bone remodeling related to dysregulation of osteoblasts and osteoclasts plays key roles in the OA initiation and development. 82 87 Increased subchondral bone porosity and remodeling, reduced bone density, and bone mineralization with irregular matrix organization, which were believed to be stimulated by bone-cartilage crosstalk through subchondral pores and vascular invasion, were observed in the early stage of OA. 88 91 These changes in subchondral bone were found to be happening at the same time with or earlier than the early destruction of articular cartilage.…”
Section: Pathogenesismentioning
confidence: 99%
“…MDSCs mainly generate where myelopoiesis takes place including the bone marrow, spleen, and other lymphatic organs, but they can be also reprogrammed from mature myeloid cells in the periphery (37). Besides their immune modulatory ability, MDSCs can differentiate into mature and functional osteoclasts (61)(62)(63)(64)(65). An in vitro experiment using murine Gr1+CD11b+ MDSCs showed that a combination of RANKL and M-CSF can initiate differentiation into osteoclasts.…”
Section: Potential Interactions Of Mdscs With Osteoclastsmentioning
confidence: 99%